Investigating the Concept of “Flirting” as Reflected in the Russian-Speaking Ukrianians’ Linguistic Consciousness - Ія Гордієнко-Митрофанова; Юлія Кобзєва; Денис Гоголь (Психолінгвістика)
The purpose of this study is to define and describe the semantic components of the verbalised concept “flirting” as a component of ludic competence in the linguistic consciousness of the Russian-speaking people from Eastern Ukraine.